2017
DOI: 10.1016/j.jcps.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Conforming conservatives: How salient social identities can increase donations

Abstract: This research considers how common perceptions of liberals' generosity can be harnessed for increasing donations. Given conservatives' greater tendency to conform to group norms than liberals, we theorize that conformity tendencies can increase donations by conservatives when accountable to a liberal audience who share a salient identity. Specifically, conservatives donate more when they are accountable to a liberal audience with whom they have a salient shared identity (Study 1) due to their motivation for so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 43 publications
2
48
0
1
Order By: Relevance
“…Ingroups typically have greater influence on individuals than do outgroups. People are more likely to behave in a prosocial manner when norms and behavioral standards are set by an ingroup (Shang et al 2008;Hysenbelli, Rubaltelli, and Rumiati 2013), when the beneficiary is part of the ingroup (e.g., Levine et al 2005;Park and Lee 2015), and when people feel accountable to those with whom they share a broader social identity (e.g., fellow college students; Kaikati et al 2017). In addition, when people learn that a negatively viewed "dissociative" outgroup has outperformed their ingroup on a positive, prosocial action (such as water conservation or composting), consumers often increase their own positive actions (White, Simpson, and Argo 2014).…”
Section: Social Influencementioning
confidence: 99%
See 1 more Smart Citation
“…Ingroups typically have greater influence on individuals than do outgroups. People are more likely to behave in a prosocial manner when norms and behavioral standards are set by an ingroup (Shang et al 2008;Hysenbelli, Rubaltelli, and Rumiati 2013), when the beneficiary is part of the ingroup (e.g., Levine et al 2005;Park and Lee 2015), and when people feel accountable to those with whom they share a broader social identity (e.g., fellow college students; Kaikati et al 2017). In addition, when people learn that a negatively viewed "dissociative" outgroup has outperformed their ingroup on a positive, prosocial action (such as water conservation or composting), consumers often increase their own positive actions (White, Simpson, and Argo 2014).…”
Section: Social Influencementioning
confidence: 99%
“…Individual differences are strong predictors of prosocial behaviors; those high in interdependent self-construal (Winterich and Barone 2011; Duclos and Barasch 2014;Allen, Eilert, and Peloza 2018;Simpson et al 2018), moral identity (Aquino and Reed 2002;Reed and Aquino 2003;Aquino et al 2007Aquino et al , 2011Winterich et al 2013;Reed et al 2016), collective self-esteem (Shang et al 2008), religiosity (Stavrova and Siegers 2014), and public self-consciousness (White and Peloza 2009) are more likely to behave prosocially. Moreover, those with female gender identity Ross 2009, 2015), liberal political identity (Kaikati et al 2017), and from a lower social class (Piff et al 2010) have been found to demonstrate higher levels of prosocial behavior.…”
Section: Individual Selfmentioning
confidence: 99%
“…Possibly, personal purchases evoke socially normative behaviors, whereas charitable donations are based on morality. It could also be that adherence to social norms drives variety‐seeking behavior for products to diversify interests to those in a small group, but these same social norms not only drive giving (Kaikati et al., 2017), but concentrate that giving.…”
Section: Discussionmentioning
confidence: 99%
“…Research has attempted to address this nuanced question, finding that liberals give more for equity‐based rewards where conservatives give more for proportionality‐based rewards (Lee, Yoon, Lee, & Royne, 2018). Furthermore, liberals and conservatives differ in their motivation for giving, such that liberals are motivated by perceptions of their own generosity, and conservatives are motivated to conform to group norms (Kaikati, Torelli, Winterich, & Rodas, 2017). Moral foundations also help to differentiate liberals and conservatives.…”
Section: Introductionmentioning
confidence: 99%
“…In an interesting example of this concept, Kaikati et al (2017) asked politically conservative students how much of a $25 cash price they would be willing to donate to a charitable cause. Driven by a conformity motivation, when the conservative students anticipated having to discuss their response with someone who held a superordinate identity in common with them—fellow University students—they behaved consistently with the perceived norm of the group.…”
Section: Identity Structure: a Multiple‐identity Network Frameworkmentioning
confidence: 99%